Perspektywy renesansu publicznego stosowanej pedagogiki społecznej w postindustrialnej przestrzeni - Radziewicz-Winnicki, Andrzej (Pedagogika Społeczna Nova, 2021)
The author takes up a critical approach to several concepts presented in the literature of social sci- ences, on so expected problems of public rehabilitation and revitalisation during the active enggement of such subdiscipline as modern social pedagogy. He analyses the local urban space, opposed to spontaneoulness chaos and anomia accured in public structures. The paper warns againt the relin- quishment in local communities of earlier order and the whole social network. It could becme in each posttransformated cociety during the social change. The aim of the paper was to mobilise on future a public support across education and prophylaxis to avoid a lot of individual and collective traumatic and neurostic feelings.